Phase II Study to Evaluate the Efficacy and Safety of Rilotumumab and Bevacizumab in Subjects with Recurrent Malignant Glioma. (17th April 2018) - Affronti, Mary Lou; Jackman, Jennifer Gamboa; McSherry, Frances; Herndon, James E.; Massey, Elwood C.; Lipp, Eric; Desjardins, Annick; Friedman, Henry S.; Vlahovic, Gordana; Vredenburgh, James; Peters, Katherine B.
Abstract : Lessons Learned : Due to evolving imaging criteria in brain tumors and variation in magnetic resonance imaging evaluation, it is not ideal to use response rate as a primary objective. Future studies involving antiangiogenic agents should use overall survival. Disease‐expected toxicities should be considered when defining the clinical significance of an adverse event. For example, vascular thromboembolic events are common in brain tumor patients and should not be attributed to the study drug in the safety analysis. Background: Recurrent malignant glioma (rMG) prognosis is poor, with a median patient survival of 3–11 months with bevacizumab (BEV)‐containing regimens. BEV in rMG has 6‐month progression free survival (PFS‐6) of ∼40% and an objective response rate of 21.2%. BEV‐containing regimens improve PFS‐6 to 42.6%–50.3%, indicating that BEV combination therapies may be superior to single agent. Rilotumumab, a hepatocyte growth factor (HGF) antibody, inhibits angiogenesis and expression of angiogenic autocrine factors (e.g., vascular endothelial growth factor [VEGF]) by c‐Met inhibition. Combination of rilotumumab with BEV to block vascular invasion and tumor proliferation may synergistically inhibit tumor growth. Methods: Thirty‐six BEV‐naïve rMG subjects received rilotumumab (20 mg/kg and BEV (10 mg/kg) every 2 weeks. Endpoints included objective response rate (using Response Assessment in Neuro‐Oncology [RANO] criteria), PFS‐6, overall survival (OS), and toxicity. Results: Median patient follow‐up was 65.0 months. Objective response rate was 27.8% (95% confidence interval [CI]: 15.7%–44.1%). Median OS was 11.2 months (95% CI: 7–17.5). PFS‐6 was 41.7% (95% CI: 25.6%–57.0%). Most frequent treatment‐related grade ≤2 events included weight gain, fatigue, allergic rhinitis, and voice alteration; grade ≥3 events included venous thromboembolism (four patients), including one death from pulmonary embolism. Conclusion: Rilotumumab with BEV did not significantly improve objective response compared with BEV alone, and toxicity may preclude the use of rilotumumab in combination BEV regimens.